4-MCHM sorption to and desorption from granular activated carbon and raw coal. (August 2016) - Jeter, T. Scott; Sarver, Emily A.; McNair, Harold M.; Rezaee, Mohammad
Abstract: 4-Methylcyclohexanemethanol (4-MCHM) is a saturated higher alicyclic primary alcohol that is used in the froth flotation process for cleaning coal. In early 2014, a large spill of crude chemical (containing primarily 4-MCHM) to the Elk River near Charleston, WV contaminated the local water supply. Carbon filters at the affected water treatment facility quickly became saturated, and the contaminated water was distributed to nearby homes and businesses. Sorption of 4-MCHM to granular activated carbon (GAC) was studied in the laboratory using head space (HS) analysis via gas chromatography with a flame ionization detector (GC-FID). Sorption to raw coal was also investigated, since this material may be of interest as a sorbent in the case of an on-site spill. As expected, sorption to both materials increased with decreased particle size and with increased exposure time; although exposure time proved to be much more important in the case of GAC than for coal. Under similar conditions, GAC sorbed more 4-MCHM than raw coal (e.g., 84.9 vs. 63.1 mg/g, respectively, for 20 × 30 mesh particles exposed to 860 mg/L 4-MCHM solution for 24 h). Desorption from both materials was additionally evaluated. Interestingly, desorption of 4-MCHM on a mass per mass basis was also higher for GAC than for raw coal. Overall, results indicated that GAC readily sorbs 4-MCHM but can also readily release a portion of the chemical, whereas coal sorbs somewhat less 4-MCHM but holds it tightly. Highlights: GC-FID with head space analysis was used to determine 4-MCHM in water. Both granular activated carbon and raw coal can effectively sorb 4-MCHM. Desorption of 4-MCHM from activated carbon may be more significant than from coal.